Leishmania infantum isolates exhibit high infectivity and reduced susceptibility to amphotericin B. Issue 8 (6th July 2020) - Faral-Tello, Paula; Greif, Gonzalo; Satragno, Dinora; Basmadjián, Yester; Robello, Carlos
Abstract : L. infantum isolates from an outbreak of canine leishmaniasis were obtained. Drug sensitivity assays and infectivity studies show significant differences with reference strains. Abstract : Leishmaniasis is a neglected disease caused by a protozoan parasite of the Leishmania species in over 98 countries in five continents. Visceral leishmaniasis is one of the main forms of the disease and is mainly caused by Leishmania infantum, whose main vector is the dipteran Lutzomyia longipalpis. The presence of the vector in Uruguay was recorded for the first time in 2010 and an autochthonous outbreak of canine visceral leishmaniasis occurred in the northern locality of the country in 2015. We report the isolation in blood-free FBS-supplemented defined media of five isolates responsible for the referred outbreak, and characterize them in terms of their growth as promastigotes, infectivity and replication in human derived monocytes and drug resistance. Results indicate similar promastigote growth among the strains, enhanced infectivity and replication for the five strains isolated from the Uruguayan outbreak when compared with reference strains from South America, equivalent drug susceptibility for miltefosine and nifurtimox and a significant difference in IC50 values for amphotericin B between the Uruguayan strains, 3–4 fold higher than the reference strain.